Addition of trunk restraint to home-based modified constraint-induced movement therapy does not bring additional benefits in chronic stroke individuals with mild and moderate upper limb impairments: A pilot randomized controlled trial - Lima R.C.M. (2014)
© 2014 IOS Press and the authors. All rights reserved.METHODS: A pilot randomized double-blinded clinical trial was conducted. Twenty-two participants with chronic stroke were randomly assigned to an experimental group that received mCIMT plus trunk restraint, or a control group (only mCIMT). Primary outcomes were the amount of use and quality of movement of the paretic upper limb (UL), determined by the Motor Activity Log (MAL) scores. Secondary outcomes included the observed performance of the paretic UL during unimanual and bimanual tasks, kinematics of reaching, strength, and quality of life. RESULTS: Both groups demonstrated significant improvements in the MAL scores and in the time to perform bimanual activities immediately after the interventions. However, no between-group differences were observed.CONCLUSIONS: The addition of trunk restraint to mCIMT resulted in no additional benefits, compared with mCIMT alone with stroke individuals with mild to moderate impairments. Unimanual and bimanual improvements were observed after mCIMT, regardless of trunk restraint, and the intervention did not adversely affect their reaching patterns.BACKGROUND: People with stroke excessively move their trunk, when reaching and grasping objects.OBJECTIVE: To determine if the addition of trunk restraint to modified constraint-induced movement therapy (mCIMT) was better than mCIMT alone in improving strength, function, and quality of life after stroke.